The southern side of paradise : [large type] a novel - Harvey, Kristy Woodson (Harvey, Kristy Woodson. Peachtree Bluff novel., 2019)
"With the man of her dreams back in her life and all three of her daughters happy, Ansley Murphy should be content. But she can't help but feel like it's all a little too good to be true. Meanwhile, youngest daughter and actress Emerson, who is recently engaged and has just landed the role of a lifetime, seemingly has the world by the tail. Only, something she can't quite put her finger on is worrying her--and it has nothing to do with her recent health scare. When two new women arrive in Peachtree Bluff--one who has the potential to wreck Ansley's happiness and one who could tear Emerson's world apart--everything is put in perspective. And after secrets that were never meant to be told come to light, the powerful bond between the Murphy sisters and their mother comes crumbling down, testing th"--